2015
DOI: 10.1016/j.ajog.2015.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime physical activity and female stress urinary incontinence

Abstract: Objective To estimate whether moderate/severe stress urinary incontinence (SUI) in middle-aged women is associated with overall lifetime physical activity (including leisure, household, outdoor, and occupational), as well as lifetime leisure (recreational), lifetime strenuous and strenuous activity during the teen years. Study design Recruitment for this case-control study was conducted in primary care level family medicine and gynecology clinics. 1538 enrolled women ages 39–65 years underwent a Pelvic Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 48 publications
4
40
0
8
Order By: Relevance
“…Because this behaviour seems to have persisted in the last two decades, there is a need to implement educational programs for healthcare providers, fitness instructors and coaches 15. Some studies indicates that presence of UI at a young age40 41 and strenuous activity during teen years42 may be a risk factor for later UI. Hence, interventions to prevent and treat the condition at an early stage is important 5.…”
Section: Discussionmentioning
confidence: 99%
“…Because this behaviour seems to have persisted in the last two decades, there is a need to implement educational programs for healthcare providers, fitness instructors and coaches 15. Some studies indicates that presence of UI at a young age40 41 and strenuous activity during teen years42 may be a risk factor for later UI. Hence, interventions to prevent and treat the condition at an early stage is important 5.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, several studies have shown that current leisure activity is associated with lower odds of SUI while lack of exercise increases these odds. 3032 After adjusting for confounders, habitual walking decreases the odds of SUI by roughly one-half in older women from various ethnic backgrounds. 33,34 …”
Section: Physical Activity and Urinary Incontinencementioning
confidence: 99%
“…40 In a large cross-sectional study in which middle-aged women recalled PA during the teen years, those that reported very high levels of strenuous PA as teenagers (more than 7.5 hours per week) had increased odds of reporting SUI in middle age; subsequent strenuous activity adjusted for teen strenuous activity was not associated with SUI. 32 The teen years may represent a particularly vulnerable time period, given the dramatic changes in hormones, muscle and bone structure and weight. Given increased risk for connective tissue injury during adolescence in girls 41 , it is biologically plausible that high strenuous activity during this period may affect future pelvic floor function.…”
Section: Physical Activity and Urinary Incontinencementioning
confidence: 99%
“…Other studies claim that the practice of moderate physical activity can minimize the reduction in the strength of pelvic floor muscles 11 or even reduce the occurrence of UI with increasing age 12 . Thus, it was observed that the level of scientific evidence on the influence of physical activity on urinary incontinence is still undefined and bidirectional 13 , as it may be a risk factor (OR = 1.37; CI 95% = 1.09-0.71) 15 or a protection factor for urinary incontinence (OR = 0.62; CI 95% = 0.44-0.89) 14 . Moreover, according to the theoretical model proposed by Nygaard et al 13 , the fact that the influence of physical activity on UI and vice versa is controversial is also due to the use of different public targets with distinct risk factors and levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%